Towards good governance - Siddiqui, Tasneem Ahmad (Oxford University Press, 2001)
At the time of partition, Pakistan showed great promise of economic development and social change. It had a hard-working and enterprising work force, a sound administration system, and good physical infrastructure. Today, fifty-one years later, Pakistan faces multi-dimensional crises. What are the basic causes of its regression and continued under-development? The author argues that Pakistan can come out of its recurring cycle of crises if there is a paradigm shift in their planning and development processes. He advocates strengthening instruments of local governance and people's participation at all levels